An Action Research Project by Teacher Candidates and their Instructor into using Math Inquiry: Learning about Relations between Theory and Practice - Paul Betts; Michelle McLarty; Krysta Dickson (Networks: An Online Journal for Teacher Research, 2017)
This paper reports on what two teacher candidates and their instructor learned from an action research project into the use of inquiry to teach mathematics. We use a model of the relation between theory and practice in teacher education to interpret what we learned about inquiry. This model describes three modes for teacher candidates to learn about teaching: (1) applying theory to practice; (2) interpreting theory and practice, and (3) building/refining personal, practical and professional theories. We learned to (1) apply the 4D-Cycle Model of inquiry, (2) interpret what it means for inquiry to be flexible, and (3) build a theory of teaching with inquiry based on non-linear and community-based dispositions of teachers toward learning. We conclude by suggesting that this model could constitute a developmental pathway by teacher candidates for experiencing the linkages between theory and practice.